ALKALOSIS RESPIRATORIK SEBAGAI PREDIKTOR PERBURUKAN OUTCOME KLINIS PADA STROKE AKUT - , An An, Dr. dr. Ismail Setyopranoto, Sp.S(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Acute stroke often causes medical problems, especially problems of acid base disorders in blood gas analysis in the form of respiratory alkalosis. Various study on the prognosis of acute stroke associated with respiratory pattern and blood gas analysis showed that hyperventilation, respiratory alkalosis, and high PH arterial blood gas analysis results assosiated with a poor prognosis. Respiratory alkalosis that occurs in acute stroke associated with increasingly poor neurological outcome. Research about respiratory alkalosis as a predictor of worsening clinical outcome in acute stroke has not been obtained in the literature with a study population of Indonesia. The aims of this study to determinewhether respiratory alkalosis as a predictor of worsening clinical outcome in acute stroke.This study used a case control design. Sampling has done with a concecutive after it adapted to inclusion or exclusion criteria.The study was conducted at unit medical record for patients who on admission to Dr. Sardjito general hospital for treatingina strokeunitorneurologicalward. The results of bivariate analysis followed by multivariate analysis with logistic regression.We obtained110 sampleof acutestrokepatientswith 55 patients with blood gas analysis respiratory alkalosis and 55 patients with normal blood gas analysis. In patients with worsening outcomes obtained 80,6 % (54 patients) with respiratory alkalosis blood gas analysis and a statistically significant difference of worsening outcomes compared to patients with normal blood gas analysis (OR =4,154, CI 95%= 2,580- 6,689, p=0,000). The worsening outcome with the highest OR = 4,231 in acute stroke patients with blood gas analysis uncompensated respiratory alkalosis of acute stroke patients than normal blood gas analysis. The resultsof multivariate analysisobtained respiratory alkalosis blood gas analysis have a significant odds ratio for worsening outcomes than other variables (OR= 345,003, p=0,000). Respiratory alkalosis is a significant predictor of worsening outcomes in patients with acute stroke.